Experimental economics : how we can build better financial markets - Miller, Ross M.; Miller, Ross M. (New York : Wiley, 2002)
An account of the new developments in economics: the scientific roots of modern finance and modern financial institutions; and the complex economic principles that govern our world of finance--P. [4] of cover.
Bubbles and experiments: Wind tunnel markets; Bargain hunting; A tale of two Smiths; Bubbles in the lab; Bubbles in the wild -- Inside markets, options, information, and liquidity: Black Monday; All the world's an option; Invisible hand discovers prices; Sending signals and keeping score; It all comes down to money -- Gridlock and the road to smart markets: Market is tied up in knots; Making markets intelligent; Smart auction block; Good intentions.
Originally published: Paving Wall Street : experimental economics and the quest for the perfect market. New York : Wiley, c2002.
"Chronology of major events": p. xix-xxii.
Includes bibliographical references (p. [287]-302) and index.
Keywords: Stock exchanges; Options (Finance); Capital market; Experimental economics; Economics